Dose-Response Studies on the Effect of n-3 Polyunsaturated Fatty Acids on Lipids and Haemostasis - Berg Schmidt, E; Varming, K; Ernst, E; Madsen, P; Dyerberg, J (Thrombosis and Haemostasis, 1990)
We have studied the dose-response effects of dietary supplementation with n-3 polyunsaturated fatty acids (n-3 PUFA’s) on lipids and haemostasis. Ten healthy males were each given 1.3 g,4 g or 9 g of n-3 PUFA’s daily for 6-week periods. Bleeding time, HDL-cholesterol and plasminogen activator inhibitor increased with the dose of n-3 PUFA. Plasma fibrinogen and triglyceride levels were reduced in a dose-dependent fashion.After ingestion of 1.3 g of n-3 PUFA’s plasma fibrinogen decreased from 9 to 7 μmol/l and HDL-cholesterol increased from 1.2 to 1.3 mmol/l. The bleeding time was prolonged from 5 to 6.5 min while triglyceride levels decreased from 1.2 to 0.9 mmol/l after ingestion of 4 g of n-3 PUFA’s. Dietary supplementation with the highest daily dose (9 g) reduced plasma levels of triglycerides, fibrinogen and von Willebrand factor, while bleeding time, plasminogen activator antigen, plasminogen activator inhibitor and the ratio of HDL-cholesterol to total cholesterol increased.
Keywords: n-3 fatty acids; Fish oil; Dose-response; Lipids; Haemostasis